A nonabelian particle-vortex duality - Murugan, Jeff; Nastase, Horatiu [UNESP] (Elsevier, 2016)
We define a nonabelian particle-vortex duality as a 3-dimensional analogue of the usual 2-dimensional worldsheet nonabelian T-duality. The transformation is defined in the presence of a global SU(2) symmetry and, although derived from a string theoretic setting, we formulate it generally. We then apply it to so-called semilocal strings in an SU(2)G×U(1)L gauge theory, originally discovered in the context of cosmic string physics.